Progesterone and Estrogen Receptors in Neurofibromas of Patients with NF1 - Mauro Geller; Spyros G.E. Mezitis; Fabio Pereira Nunes; Marcia G. Ribeiro; Alexandra Prufer de Q.C. Araújo; Marcello D. Bronstein; Rodrigo Siqueira-Batista; Andréia Patrícia Gomes; Lisa Oliveira; Karin Soares Gonçalves Cunha (SAGE Publishing, 2008)
Neurofibromatosis type 1 (NF1) or von Recklinghausen disease is a genetic disorder affecting the growth of cells in nervous system. One of the most remarkable characteristics of this disease is the development of benign tumors of the nervous system (neurofibromas). The purpose of this study was to test tissue samples taken from neurofibromas and plexiform neurofibromas of NF1 patients for the presence of estrogen and progesterone receptors. We used previously collected samples from patients registered in the database of the Centro Nacional de Neurofibromatose (CNNF-Brazil). Samples from twenty-five patients in the database presenting plexiform neurofibromas (N1 group) and 25 samples from the same database from patients presenting neurofibromas (N2 group) were tested. We observed positive staining for progesterone receptors in 13 of the neurofibroma samples and 19 of the plexiform neurofibroma samples. Among the neurofibroma samples, we observed one sample with positive estrogen receptor staining, but none of the plexiform neurofibroma samples showed positive staining. We suggest further studies to investigate in greater depth possible hormonal influences on the development and growth of neurofibromas and plexiform neurofibromas in NF1.